Efektivitas Bantuan Sosial Satuan Gugus Tugas Percepatan Penanganan Corona Virus Disease 2019 (Covid-19) Kabupaten Indragiri Hilir - Putri Angellia Perdana; Mimin Sundari Nasution (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
The Indragiri Hilir Regency Covid-19 Task Force provides social assistance to communities affected by covid-19. However, this assistance program did not run effectively because the objectives of this social assistance had not been achieved. The purpose of this social assistance is to ease the burden on the community in the midst of the covid-19 pandemic situation. This study aims to determine the effectiveness of social assistance for the Covid-19 task force in Indragiri Hilir Regency. The theory that the researcher uses is the effectiveness of the program according to Budiani in Nuraida 2019 which has indicators, namely the accuracy of program targets, program socialization, program objectives, and program monitoring. The research method used is qualitative with data collection techniques through interviews, observation, and documentation. In realizing the effectiveness of social assistance, there are still several inhibiting factors, such as goals that have not been achieved so that there are still people who do not receive assistance, socialization related to social assistance is not optimal so that many people do not know about this assistance, and the task force unit is less responsive in implementing social assistance. distribute social assistance so that there are still people who do not receive assistance. The results showed that the effectiveness of the social assistance task force unit for the acceleration of handling the 2019 corona virus disease in Indragiri Hilir Regency had not been effective.